Implementasi Media Canva dalam Pembelajaran Bahasa Indonesia Teks Surat Pribadi dan Dinas pada Siswa SMPN 34 Semarang - Rochimmatussa’adah; Rifana Yuniartanti; Neni Widyawati; Fahrizal Lalang Sitoro; Asep Purwo Utomo; Isnarto Isnarto; Slamet Hari Pambudi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Along with the times, the use of interactive learning media technology is needed to increase learning motivation. Students will be more interested in the new learning process. This is shown through the active involvement of students in the learning process. This study aims to describe the implementation of Canva media in learning Indonesian personal and official letter texts to Students of SMPN 34 Semarang. The research method used is descriptive qualitative research method. Qualitative descriptive method is a method whose research data is in the form of descriptive notes. The data collection technique in this study is through a questionnaire. Data were analyzed by means of data reduction and drawing conclusions. The results showed that the implementation of Canva media in learning Indonesian personal and official letter texts to SMPN 34 Semarang students could be concluded that students' learning motivation increased after using Canva learning media. There were 26 students with a percentage of 85% who said Canva's learning media was very useful and 4 students with a percentage of 15% said it was useful. So it can be concluded that the use of Canva media is very useful in increasing learning motivation in achieving the learning objectives of Indonesian personal and official letter texts. This is shown through students being actively involved and cooperative in the learning process. In addition, students are able to produce written products in the form of personal and official letters through Canva media.